Pengukuran Kinerja Rantai Pasok Halal dengan Pendekatan Supply Chain Operation Refrence (SCOR) pada PT. Soka Cipta Niaga - Kara Aina Rinika; Aviasti (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. The halal industry sector in Indonesia has experienced a very rapid increase. Based on the Global Islamic Economic Conditions Report (SGIE) 2020/2021, the halal fashion industry sector in Indonesia is ranked 3rd, this causes increasingly tight competitiveness, so that companies must excel in competing. Constraints experienced by the company are delays in raw materials from suppliers in terms of quality, quantity and time. The goal in achieving competitive advantage is to measure supply chain performance from upstream to downstream so that companies can find out which performance indicators need to be maintained and which need to be improved. The method used to improve the company's performance is the Supply Chain Operation Reference (SCOR) method. Performance measurement is carried out by mapping the halal supply chain using the SCOR method at level 1, level 2 and level 3. Next, a pairwise comparison questionnaire is distributed and each indicator is calculated using the Analytical Hierarchy Process (AHP) approach and normalization is calculated using the snorm de boer formula. So that the final value of supply chain performance is obtained at 63.54 which indicates this value is included in the average category. The conclusion that can be drawn is that the company knows which performance indicators need to be improved and which need to be maintained so that the company can improve performance from the results of supply chain performance measurements. Abstrak. Sektor industri halal di Indonesia mengalami peningkatan yang sangat pesat. Berdasarkan Laporan Kondisi Ekonomi Islam Global (SGIE) 2020/2021, sektor industri fashion halal di Indonesia menginjak peringkat ke-3 hal tersebut menyebabkan adanya daya saing yang semakin ketat sehingga membuat perusahaan harus unggul dalam bersaing. Kendala yang dialami perusahaan yakni adanya keterlambatan bahan baku dari pemasok baik dari sisi kualitas, kuantitas dan waktu. Tujuan dalam mencapai keunggulan bersaing yaitu dengan mengukur kinerja rantai pasok mulai dari hulu hingga hilir agar perusahaan dapat mengetahui indikator kinerja yang perlu untuk dipertahankan dan yang perlu untuk dilakukan perbaikan. Metode yang digunakan untuk meningkatkan kinerja perusahaan yaitu metode Supply Chain Operation Reference (SCOR).Pengukuran kinerja dilakukan dengan memetakan rantai pasok halal dengan metode SCOR pada level 1, level 2 dan level 3. Selanjutnya dilakukan penyebaran kuesioner perbandingan berpasangan lalu dihitung setiap indikator dengan pendekatan Analitical Hierarchy Process (AHP) dan menghitung normalisasi dengan rumus snorm de boer. Sehingga nilai akhir kinerja rantai pasok didapat sebesar 63,54 yang menunjukan nilai tersebut termasuk kategori rata-rata. Kesimpulan yang dapat diambil yaitu perusahaan mengetahui indikator kinerja mana yang perlu dilakukan perbaikan dan yang perlu untuk dipertahankan sehingga perusahaan dapat meningkatkan kinerja dari hasil pengukuran kinerja rantai pasok.